The role of protected areas in the formation of a comfortable urban environment formation - G. Yu. Morozova; I. D. Debelaya (Юг России: экология, развитие)
Aim: to determine the importance of protected areas (PA) in the formation of a comfortable urban environment formation.Methods. The following activities have taken place: collection of the route‐floristic descriptions, inventory of plantations, analysis of regulatory and stock materials, determination of the relative living condition of stands and calculation of ecosystem services.Results. PAs as unique natural objects have become a counterbalance to aggressive urban environments and serve as a tool for stabilising the ecological state of a territory as well as for keeping its population healthy. For the first time, in accordance with a systematic approach, the role of protected areas in different parts of urban life that define the comfort of an urban environment was analysed. The network of PAs of Khabarovsk includes 29 objects with a total area of 585.45 ha, which amounts to 1.51% of the total city area. The PA’s specifics were determined according to the urban planning and economic development of the territory and were divided into 6 categories: natural recreational complexes, nurseries, park zones, natural monuments, nature parks and public gardens. According to the systematic approach, we have analysed the role of protected areas in the formation of a comfortable urban environment for Khabarovsk. The example of the “Orekhovaya Sopka”, a protected area of local importance with an ability to intercept water in the form of precipitation, made it possible to increase the economic and ecological value of the protected urban lands in ecosystem service calculations.Conclusions. Urban PAs are protected natural objects with multipurpose use. The main function of PAs is to form a comfortable urban environment which is closely intertwined with architectural and urban planning and the economic, social and environmental spheres of urban life. The insignificant share of PAs in the total area of Khabarovsk indicates the necessity to expand their areas. It is proposed to use the indicator "PA’s share in the total area of a city" in urban environment quality index development.